2021
DOI: 10.1093/jxb/eraa602
|View full text |Cite
|
Sign up to set email alerts
|

The front line of defence: a meta-analysis of apoplastic proteases in plant immunity

Abstract: Secreted proteases act at the front line of defence and play pivotal roles in disease resistance. However, the criteria for apoplastic immune proteases are not always defined and followed. Here, we critically reviewed 46 apoplastic proteases that function in plant defence. We found that most apoplastic immune proteases are induced upon infection and seventeen proteases are genetically required for the immune response. Proteolytic activity has been confirmed for most of the proteases but is rarely shown to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 134 publications
0
24
0
Order By: Relevance
“…In an elegant study, Zimmermann et al ( 2016 ) showed that P69B promoted cell death in tomato, although the overexpression of P69B alone could not. Thus, control over PCD is an undoubtedly important aspect of defense responses, and apoplastic subtilases form an integral part of its control, although additional proteases also participate (Godson and van der Hoorn, 2021 ). Investigations aimed at determining whether these subtilases display caspase-like activity would be highly informative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an elegant study, Zimmermann et al ( 2016 ) showed that P69B promoted cell death in tomato, although the overexpression of P69B alone could not. Thus, control over PCD is an undoubtedly important aspect of defense responses, and apoplastic subtilases form an integral part of its control, although additional proteases also participate (Godson and van der Hoorn, 2021 ). Investigations aimed at determining whether these subtilases display caspase-like activity would be highly informative.…”
Section: Discussionmentioning
confidence: 99%
“…Markedly, SCLPs are known to contain signal peptides and are quite often found in the apoplast (Fraser et al, 2005 ; Sueldo et al, 2014 ; Grosse-Holz et al, 2018 ). Similarly, MMPs from the M10 family in plants have all been described as containing signal peptides and are the only metalloproteases in plants that are classed as apoplastic (Godson and van der Hoorn, 2021 ). Therefore, it is interesting to note that all but one DE avocado apoplastic metalloprotease coding gene was predicted to belong to the M10 MMP family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secreted proteases have been proposed to be involved in the digestion of the host barrier, such as the crayfish cuticle in the case of Aphanomyces astaci [98], or the human epidermis in the case of Pythium insidiosum [99]. However, it is assumed that proteolysis of plant substrates is a strategy employed by plant pathogens during the infection process [100,101], meaning most of the proteases predicted in Phytophthora sp. contribute to pathogen virulence [102,103].…”
Section: Discussionmentioning
confidence: 99%
“…The tissue defense responses include stomatal closure and callose deposition (Zhou et al 2013). The molecular defenses include the secretion of antimicrobial substrates such as antimicrobial peptides, phytoalexins and apoplastic proteases (Ebel 1986;Ahuja et al 2012;Campos et al 2018;Godson and Hoorn 2021).…”
Section: Introductionmentioning
confidence: 99%